(untitled) (University of Khartoum Engineering Journal, 2022)
The main aim of the research presented in this paper is to evaluate the impact and influence of different interpolation methods on the quality of the derived digital elevation model (DEM). The main factors affecting the quality of the DEM are: the data sampling method, data density, terrain complexity, and the interpolation method and interpolation parameters. This paper is set answer two main questions: what is the best interpolation method thatcould be used to generate a DEM to satisfy the accuracy level required for a certain application? Upon what criteria an interpolation method could be chosen? To answer such questions an investigation was carried out on digital elevation models generated from different data sources using different interpolation methods. Three data sets andthree interpolation methods were used in the investigation. The results clearly revealed the role of the interpolation method selection on the quality of the generated DEM, in general and in particular DEMs generated from data sets of low density and biased distribution. The investigation also showed the important role of the interpolation parameters in the performance of the interpolation method.